Health promotion groups in primary education focusing on the use of alcohol and other drugs - Souza Faria, Victor Gabriel; de Freitas Moraes, Bianca; Souza de Almeida, Camila (Guará Journal, 2019)
University outreach brings the university closer to the community, contributing to the development of both the students involved and the community. This article describes and discusses the outreach experience of psychology students at the State University of Minas Gerais in a project promoting health and the use of alcohol and other drugs with ninth-grade students. This descriptive, qualitative study, using an experience report approach, involved group work at a public school in a city in the interior of Minas Gerais. The meetings took place over a four-month period, with biweekly meetings, from August to November 2017. The topics and techniques used were diverse, focusing on capturing the interest and attention of adolescents. The topics were chosen by the adolescents themselves at the end of each meeting. Topics covered included violence, prejudice, respect, and the use of alcohol and other drugs. Techniques ranged from discussion groups to theatrical techniques. The project achieved its purpose of awakening students’ interest in topics often considered taboo and giving voice to their doubts and questions.